Health economics for low-income countries - Germano Mwabu (Yale University, Economic Growth Center, 2007)
Good health is a determinant of economic growth and a component of well-being. This paper discusses and synthesizes economic models of individual and household behavior, showing how they may be used to illuminate health policy making in low-income countries. The models could help address questions such as: How can the health of the poor be improved, and what are the economic consequences of better health? What policies would improve intra-household distribution of health outcomes? An extensive literature on health human capital and household models, and on related field experiments is reviewed in an attempt to answer these questions. It is found that there are large returns to health improvements in low-income countries. Moreover, health improvements in poor nations can be achieved through implementation of simple interventions such as dietary supplements, control of parasitic diseases, and pro-poor social expenditures. The paper concludes with a discussion of these policy options.
Keywords: I12; I11; D13; O12; 330; Health production; health care markets; household production and intrahousehold allocation; health economics; low-income countries.